Complete mitochondrial DNA genome sequences from the first New Zealanders - Knapp, Michael (National Academy of Sciences, 2012)
The dispersal of modern humans across the globe began ∼65,000 y ago when people first left Africa and culminated with the settlement of East Polynesia, which occurred in the last 1,000 y. With the arrival of Polynesian canoes only 750 y ago, Aotearoa/New Zealand became the last major landmass to be permanently settled by humans. We present here complete mitochondrial genome sequences of the likely founding population of Aotearoa/New Zealand recovered from the archaeological site of Wairau Bar. These data represent complete mitochondrial genome sequences from ancient Polynesian voyagers and provide insights into the genetic diversity of human populations in the Pacific at the time of the settlement of East Polynesia.